2017 IEEE/ACM 39th International Conference on Software Engineering (ICSE) 2017
DOI: 10.1109/icse.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Becoming Agile: A Grounded Theory of Agile Transitions in Practice

Abstract: Agile adoption is typically understood as a oneoff organizational process involving a staged selection of agile development practices. This view of agility fails to explain the differences in the pace and effectiveness of individual teams transitioning to agile development. Based on a Grounded Theory study of 31 agile practitioners drawn from 18 teams across five countries, we present a grounded theory of becoming agile as a network of on-going transitions across five dimensions: software development practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 30 publications
2
77
0
6
Order By: Relevance
“…Our study supports the different levels of autonomy evident on agile teams [11] as we found evidence of varying management approaches: manager-driven, managerassisted and team-driven. Additionally, we also identified a new level: individual-driven task allocation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study supports the different levels of autonomy evident on agile teams [11] as we found evidence of varying management approaches: manager-driven, managerassisted and team-driven. Additionally, we also identified a new level: individual-driven task allocation.…”
Section: Discussionsupporting
confidence: 86%
“…With the evolution of agile methods, software teams are meant to be self-organizing with high levels of autonomy, teams empowerment and mutual decision making in their everyday work [10,12] including project management activities such as task allocation [11,12]. In practice, however, agile teams are seen to display varying levels of autonomy as they gain experience of functioning in a self-organizing way [11].…”
Section: Related Workmentioning
confidence: 99%
“…Part of this training is to discuss impediments with the team and resolve resentments . The core of an agile transformation is to change the culture of the company . This change is strongly facilitated by a thorough training …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the concepts of 'light touch' management and self-organizing teams are the essence of agile teams [1]. These benefits have taken many software firms by a storm, as a result adopting many of these practices in their everyday project management activities including task allocation [4,8]. This has affected the way the tasks allocation takes place in agile teams.…”
Section: Related Workmentioning
confidence: 99%
“…Self-directed task allocation or self-assignment is an attribute of agile teams [4,8]. In theory, every member of the agile team is meant to assign a task or user story to themself [4].…”
Section: Related Workmentioning
confidence: 99%